Kinetic analysis suggests that malathion at low environmental exposures is not toxic to humans - Lawrence M. Schopfer; Ozden Tacal; Patrick Masson; Oksana Lockridge (PLoS ONE, 2025)
Malathion has the reputation of being a safe pesticide. There are no reported cases of cholinergic toxicity in people exposed to low environmental doses of malathion. Our goal was to explain the safety of malathion in terms of the mechanism of malathion detoxication. The structure of malathion includes a built-in safety feature, specifically two ethyl esters. The ethyl esters are decarboxylated by human esterases to negatively charged malathion which does not react with acetylcholinesterase. Acetylcholinesterase is the toxicologically relevant target for organophosphates such as malathion. A toxic form of malathion is produced by Cytochrome P450 enzymes which convert malathion to malaoxon. Malaoxon is toxic because it inhibits acetylcholinesterase. We used high pressure liquid chromatography on a Prodigy 5 µm ODS column to monitor the production of enzyme-catalyzed decarboxylation of the malathion ethyl esters. The products of malathion decarboxylation were identified by mass spectrometry using a Thermo RSLC Ultimate 3000 ultra-high pressure chromatography system with a Thermo Easy-Spray PepMap RSLC C18 separation column attached to an Orbitrap Fusion Lumos Tribrid mass spectrometer. Decarboxylation and enzyme inhibition were assayed with recombinant human acetylcholinesterase (rHuAChE), human butyrylcholinesterase (HuBChE), and recombinant human liver carboxylesterase (rHuCE1). A trace contaminant in 98.5% pure malathion was identified by mass spectrometry. Consistent with the fact that negatively charged compounds are not inhibitors of HuAChE, HuBChE, or HuCE1, we found that negatively charged, decarboxylated malathion did not inhibit the activity of rHuAChE, HuBChE, or rHuCE1. Carboxylesterase detoxified malathion 100,000-fold faster compared to rHuAChE and HuBChE. Low dose exposures to malathion are not directly toxic The toxic metabolite, malaoxon, is produced very slowly. By comparison, detoxified malathion acids are formed rapidly. In conclusion, our data suggest that the safety of low dose environmental exposures to malathion is explained by the fact that malathion is detoxified faster than it is activated to the toxic malaoxon. Our review of the literature finds no convincing evidence that low dose malathion exposure causes cancer.